PARENTING PATTERNS AND CHILDREN'S LEARNING MOTIVATION ARE RELATED TO CHILDREN'S LEARNING OUTCOMES IN ELEMENTARY SCHOOL CHILDREN (GRADE 6) AT SDN CIRACAS 10 PAGI - Hapsari, Eka Cahya; Sulastri, Titi; Hapsari, Dina Carolina; Ningsih, Ratna (Jurnal Keperawatan, 2025)
Learning achievement results are an indicator of the quality and quantity of knowledge obtained by students and see the ability of students. Every child has the ability to achieve good learning achievement, but in reality there are many obstacles that prevent children from achieving this. One of them is parenting and children’s learning motivation. Children who get the right parenting style and have good self-motivation will affect good learning achievement as well. Purpose: This study aims to analyze the relationship between parenting patterns and children’s learning achievement results at SDN Ciracas 10 Pagi and analyze the relationship between children’s learning motivation and children’s learning achievement results at SDN Ciracas 10 Pagi. Methods: This study used a correlational analytic design with a cross sectional approach, purposive sampling technique. The sample in this study amounted to 66 respondents and respondents of 6th grade children and data analysis in this study using the spearman rank test. Research results: The results of the spearman rank analysis of parenting patterns with learning achievement results obtained a value of P= 0,000 (P<,0,05), learning motivation with learning achievement results obtained a value of P = 0,006 (P<0,05), it can be concluded that there is a relationship between parenting patterns and children’s learning achievement results (grade 6) at SDN Ciracas 10 Pagi and there is a relationship between children’s learning motivation and children’s learning achievement results (grade 6) at SDN Ciracas 10 Pagi